DIGITAL TRANSFORMATION IN INDONESIAN EDUCATION: TRENDS, COLLABORATION, AND FUTURE RESEARCH DIRECTIONS - Mela Pebriana Sari; Furtasan Ali Yusuf; Uli Wildan Nuryanto (Jurnal Manajemen Pendidikan, 2026)
This study analyzes the development of digital transformation research in Indonesian education by identifying publication trends, dominant themes, collaboration patterns, and future research directions. A bibliometric approach was applied to 479 Scopus-indexed publications published between 1978 and 2026. Data were analyzed using VOSviewer and Biblioshiny to examine publication growth, productive authors and institutions, citation patterns, thematic evolution, and keyword co-occurrence networks. Research on digital transformation in Indonesian education has grown significantly, particularly after the COVID-19 pandemic, with an annual publication growth rate of 9.93%. Dominant themes include e-learning, educational technology, online learning, digital learning systems, and higher education transformation. Emerging topics such as artificial intelligence, adaptive learning, gamification, and digital literacy reflect increasing diversification of research interests. Indonesian universities play a strategic role in advancing digital transformation research through collaborative and interdisciplinary scholarly networks. The novelty of this study lies in integrating bibliometric mapping and thematic analysis to examine the intellectual structure, thematic evolution, and future research opportunities of digital transformation in Indonesian education. The findings provide insights for developing inclusive, adaptive, and sustainable digital education ecosystems.